BLENDED LEARNING AND MOOCS a new generation education system. - Manna, Manpreet Singh; Balusamy, Balamurugan; Sharma, Meenakshi; Samuel, Prithi ([S.l.] : ROUTLEDGE, 2022)
This book presents a framework for integrating blended learning and massive open online courses (MOOCs) in the Indian education system. It argues that blended teaching and learning is the most suitable approach to education in a post-COVID-19 world. Drawing on case studies used in blended learning practices around the world, the book provides ample resources for beginners to improvise the spread of knowledge around information technology in higher education. It discusses various concepts such as flip learning in blended learning models and examines the self-assessment tools and structures it offers to institutions for building competencies. In addition to addressing the challenges and opportunities of adopting the digital mode of teaching, the book also offers techniques and concepts helpful for designing MOOCs. It covers concepts such as curriculum designing, content flow, teaching behavior, and evaluation patterns, which are important aspects of online teaching. An indispensable guide to navigating the shift from offline to online teaching, this book will be of interest to students, teachers, and researchers of education, education technology, digital education, and information technology. It will also be useful to policymakers, educational institutions, EdTech start-ups, NGOs in the education sector, and online education centers.
Keywords: Blended learning; Blended learning -- Case studies; MOOCs (Web-based instruction); MOOCs (Web-based instruction) -- Case studies; EDUCATION / General; EDUCATION / Computers & Technology; EDUCATION / Higher